Optimizing logistics costing in Malaysian small and medium enterprises: A case study of garment manufacturer - Chua, Moo Yi; Lee, Khai Loon; Nor Rokiah Hanum, Md Haron; Gusman, Nawanir (Penerbit Universiti Malaysia Pahang, 2025)
This paper addresses the critical issue of inefficient logistics costing practices within garment manufacturing small medium enterprises (SMEs) in Malaysia, which often leads to suboptimal cost management and competitive disadvantage. It investigates the current practices of logistics costing in local garment manufacturing SMEs and examines the challenges posed by emerging trends in logistics costing. The study also aims to identify prevalent practices in logistics management, ascertain the factors influencing logistics costs, and recommend effective strategies for optimising these costs. A qualitative method via semi-structured interview was employed to gather the data. The findings reveal that logistics costs are predominantly calculated based on transportation fees alone. Significant factors affecting logistics costs include currency exchange rates and labour expenses. The recommended best practices for managing logistics costs effectively include outsourcing logistics functions and opting for smaller vehicles, such as cars or vans, instead of larger lorries.